2013
DOI: 10.1063/1.4812668
|View full text |Cite
|
Sign up to set email alerts
|

In situ analyses on negative ions in the indium-gallium-zinc oxide sputtering process

Abstract: The origin of negative ions in the dc magnetron sputtering process using a ceramic indium-gallium-zinc oxide target has been investigated by in situ analyses. The observed negative ions are mainly O− with energies corresponding to the target voltage, which originates from the target and barely from the reactive gas (O2). Dissociation of ZnO−, GaO−, ZnO2−, and GaO2− radicals also contributes to the total negative ion flux. Furthermore, we find that some sputtering parameters, such as the type of sputtering gas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 24 publications
0
26
0
Order By: Relevance
“…In this study, off-axis sputtering was used to confirm this possible mechanism. In general, negative oxygen ions are considered to be the origin of the bombardment effect because of their high energy (approximately several hundred electron volts) [6]. In the sputtering process, negative oxygen ions are accelerated by the cathode sheath and move towards the substrate in a straight path; thus, the bombardment effect from the high-energy particles should be observed in the facing position, as shown in Fig.…”
Section: Bombardment Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, off-axis sputtering was used to confirm this possible mechanism. In general, negative oxygen ions are considered to be the origin of the bombardment effect because of their high energy (approximately several hundred electron volts) [6]. In the sputtering process, negative oxygen ions are accelerated by the cathode sheath and move towards the substrate in a straight path; thus, the bombardment effect from the high-energy particles should be observed in the facing position, as shown in Fig.…”
Section: Bombardment Effectmentioning
confidence: 99%
“…Sputtering deposition can be used to produce uniform TiO 2 thin films with a large area, high packing density and strong adhesion [1,6]. However, TiO 2 films deposited by magnetron sputtering are often a mixture of anatase and rutile phases.…”
Section: Introductionmentioning
confidence: 99%
“…Our recent supercomputer simulations suggested that atomic particles considered to be sputtered from the target like pellets are likely to be adsorbed on the side of pellets rather than the top. Presumably, the surfaces of pellets are negatively charged in the plasma atmosphere [11] [12]. According to this assumption, we propose a mechanism shown in Figure 4 [13].…”
Section: Crystal-deposition Modelmentioning
confidence: 74%
“…It was reported that the energetic bombardment of negative oxygen ion, which was accelerated by the applied electric field between the substrate and the target in DC magnetron sputtering, would be the reason for the GI/channel interface damage. 26,27 Since all TFTs were fabricated under the same conditions exception for IGZO deposition temperature, it is reasonable to assume that the qualities of SiO x GIs are similar for all TFTs. On the other hand, it is also well established that trapped carriers in a GI are mainly determined by gate bias stress and GI quality.…”
Section: Resultsmentioning
confidence: 99%